2019
DOI: 10.3892/etm.2019.7973
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential key genes in esophageal adenocarcinoma using bioinformatics

Abstract: Esophageal adenocarcinoma (EAC) is the predominant pathological subtype of esophageal cancer in Europe and the USA. The present bioinformatics study analyzed a high-throughput sequencing dataset, GSE94869, to determine differentially expressed genes (DEGs) in order to identify key genes, biological processes and pathways associated with EAC. Functional enrichment analysis was performed using the Database for Annotation Visualization and Integrated Discovery. The co-expression network of the DEGs was establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Compared with normal tissues, METTL7B was reported to be expressed at high levels in ESCA [ 7 ], LUAD [ 5 ], and THCA [ 4 ]. By analyzing 27 cancer datasets, we found that METTL7B expression was upregulated in 22 tumors, including ESCA, LUAD and THCA, consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with normal tissues, METTL7B was reported to be expressed at high levels in ESCA [ 7 ], LUAD [ 5 ], and THCA [ 4 ]. By analyzing 27 cancer datasets, we found that METTL7B expression was upregulated in 22 tumors, including ESCA, LUAD and THCA, consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…METTL7B is involved in infections, hepatitis and obstetric diseases [1][2][3]. METTL7B has also been proven to be overexpressed in multiple malignancies [e.g., papillary thyroid cancer (PTC), lung cancer, and esophageal adenocarcinoma], while it is downregulated in breast cancer [4][5][6][7]. Through different mechanisms, METTL7B plays a vital regulatory role in multiple tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an unknown function, METTL7B has surfaced in several genetic studies linking its upregulation to multiple disease states 24 , 25 . Specifically, METTL7B expression is significantly altered in kidney disease, acute respiratory distress syndrome, and numerous cancers, including breast, non-small cell lung, thyroid, and ovarian 24 – 30 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we also integrate molecular docking technology, which can predict the binding degree of small molecules to targets and facilitate the screening of active components in Chinese medicines. The screening of prognostic genes for ESCA has been addressed in previous studies [ 28 ]. On the contrary, this study combines network pharmacology with bioinformatics to screen four ESCA targets.…”
Section: Discussionmentioning
confidence: 99%